A study on preferences towards patriot brand through outdoor sales (ODS) activities / Jusnita Suzlin Jusoh - Jusoh, Jusnita Suzlin (Faculty of Business and Management, 1999)
In today's highly competitive retail industry, private brand products are becoming more and more important. As department stores and specialty outlets rely less on manufacturer brands and more on promoting their own private brands. Private brands give the retailer greater control over the merchandise, more flexibility in dealing with changing trends and more control over prices. This study is undertaken to identify the most preference items for Patriot to the customers, to determine the factors that influence the customers when buying the Patriot brand and to identify other electrical items that are suggested by the customers for Patriot brand. One of the strategies that usually done by the retail outlets in order to generate sale is having sale like Blockbuster Sale for Metrojaya, The Grand Sale for Parkson and so as with PERNAMA. PERNAMA also has its sales namely Outdoor Sales (ODS) Activity.